Incidence of Kidney Stones in the United States: The Continuous National Health and Nutrition Examination Survey. Issue 4 (2nd April 2022) - Hill, Alexander J.; Basourakos, Spyridon P.; Lewicki, Patrick; Wu, Xian; Arenas-Gallo, Camilo; Chuang, Debby; Bodner, Donald; Jaeger, Irina; Nevo, Amihay; Zell, Michael; Markt, Sarah C.; Eisner, Brian H.; et al.
Abstract : Purpose: The incidence of kidney stones in the United States is currently unknown. Here, we assessed the incidence of kidney stones using recent, nationally representative data. Materials and Methods: We used the National Health and Nutrition Examination Survey (NHANES) from 2015 to 2018. During this time participants were asked, "Have you ever had a kidney stone?" and "In the past 12 months, have you passed a kidney stone?" Demographics analyzed include age, race, gender, body mass index, history of smoking, diabetes, hypertension, hypercholesterolemia and gout. Multivariable models were used to assess the independent impact of subject characteristics on kidney stone prevalence and incidence. Results: Data were available on 10, 521 participants older than age 20. The prevalence of kidney stones was 11.0% (95% CI 10.1–12.0). The 12-month incidence of kidney stones was 2.1% (95% CI 1.5–2.7), or 2, 054 stones per 100, 000 adults. We identified significant relationships between stone incidence and subject age, body mass index, race and history of hypertension. Conclusions: Here we find a substantially higher 12-month incidence of kidney stones than previous reports. We also validate known risk factors for stone prevalence as associated with incidence. The remarkable incidence and prevalence of stones is concerning and has implications for disease prevention and allocation of medical resources.